Quality of life and adherence to physical activity in leisure time of people with physical disability - Aminzadeh Reza; Khazaei Mohammad; Dzioban Katarzyna; Azizi Bahador; Dehghani Elham (Sciendo, 2024)
Study aim: People with disability are characterized by mental disorders, lower physical function, and poor social functioning. Dramatically, they are at particular risk of loss of their psychosocial functions. Here, we tested the relationship between quality of life and adherence to physical activity in leisure time of people with physical disability.